Evaluation of the capital budget planning practice of contractors in the construction industry - Famakin .I.O; Saka .N (Penerbit UKM, 2011)
Poor and unrealistic budgeting has been traced to the inefficiency and neck-deep poverty of contractors in the construction industry, this attributes to the economic decline of firms and capital disappearance in the industry. This research work seeks to evaluate the capital budget planning practice of contractors in the Nigerian construction industry. The research made use of questionnaires for data collection and the statistical tools employed in the analysis are frequency tables, percentages, cumulative percentages, and mean score ranking. The variables used for the evaluation include long-term capital budgets, capital budgeting manual/written procedures, formal bodies responsible for screening and reviewing projects, capital budgeting personnel and regular minimum rate of return review. The study revealed that about 50% of contractors do not make plan for long-term capital budgets and therefore cannot handle large projects. It is recommended that contractors make plan for long-term capital budgeting and devote more personnel to capital budget planning to ensure that they can handle the numerous large construction projects in the industry